Supply side fantasies and precarious part-time academic labor - Jacoby, Daniel; Boyette, Jonathan (Education Policy Analysis Archives, 2020)
Reliance upon part-time instructors within U. S. post-secondary institutions has received a great deal of attention, particularly as the percentage of such faculty has become the largest single category of faculty in academia. Understanding how part-time markets operate may allow better policy. Most current studies on the subject examine national markets, and emphasize demand factors motivating expansion of the part-time workforce. Although the subject of supply was once critical to discussions it has received less attention of late in part due to a faulty understanding of how part-time markets operate. Cross sectional regression analysis is performed to explore potential correlations between the number of graduating masters and doctoral students and reliance upon part-time faculty at neighboring institutions of higher education. Where previous researchers have found that institutions in more urbanized settings exhibit greater reliance upon part-time faculty, this analysis indicates that local availability of recently minted masters and PhD degrees within commuting distances of the hiring institution more closely fits staffing data. Policy actors may be able to use these results to better coordinate regional or local demand to supply, which has implications for unions and other policy actors attempting to limit reliance upon part-time faculty.